Comparative study on in vitro fertilization, cleavage and blastocyst development of post-warmed vitrified cattle oocytes in different media - Sebopela, Maleke Dimpho; Mkhize, Ntuthuko Raphael; Thema, Mamonene Angelinah; Mphaphathi, Masindi Lottus (Frontiers in Veterinary Science, 2025)
IntroductionImproving the efficiency of in vitro embryo production could be possible by optimizing the media used for oocyte cryopreservation, fertilization, and embryo culture. This study evaluated the fertilization success and developmental competence of post-warmed vitrified cattle oocytes cultured in three distinct in vitro protocols.MethodsA total of 270 immature oocytes were randomly divided into three experimental groups (n = 90 per group), each exposed to different vitrification, warming and fertilization protocols. In Group 1; oocytes were vitrified and warmed using commercial (ART Lab Solutions, Australia) medium, Group 2; oocytes were vitrified and warmed using TCM 199-based solution (prepared medium) and Group 3; oocytes were vitrified and warmed using Bioscience™ medium (IVF Bioscience, BO-VitriCool™ and BO-Vitri Warm™, United Kingdom). Post-warming, oocytes were matured in vitro per group: Group 1—Vitromat-Protect™, Group 2—TCM199, and Group 3—BO IVM™. Matured oocytes were then subjected to in vitro fertilization (IVF) using VitroFert™ (Group 1), prepared BO-IVF (Group 2) and BO-IVF™ (Group 3). Following 18 h post-IVF, presumptive zygotes were washed and cultured in VitroCleave PLUS™ (Group 1), BO IVC (Group 2) and BO IVC™ (Group 3) media. Embryos were further cultured in BO IVC, BO IVC™, or VitroBlast (Group 1) protocol with medium changes as per respective protocols. These observations were repeated 6 times.ResultsAmong vitrified oocytes, BO IVF™ achieved the highest total (35.33 ± 3.61) and normal fertilization rates (42.66 ± 9.43), significantly higher than VitroFert™ and BO IVF. Non-vitrified oocytes showed no significant fertilization differences across media but consistently had higher cleavage rates (38.83–55.28%) than vitrified oocytes (26.50–30.00%). Embryos from non-vitrified oocytes cultured in BO IVC™ reached the highest morula (31.14 ± 6.17) and blastocyst (29.57 ± 6.97) development, whereas embryos from vitrified oocytes cultured in VitroCleave Plus™ yielded the highest morula and blastocyst rates (18.33 ± 15.7) compared with BO IVC™ (12.16 ± 14.14) and BO IVC (9.66 ± 15.18; p < 0.05).ConclusionBO IVF™, and VitroCleave Plus™ medium demonstrated potential for enhancing post-warmed oocyte competence and fertilization, cleavage and blastocyst outcomes compared to other treatment groups. Although vitrification reduces fertilization and development, VitroCleave Plus™ appears to offer the optimal support for post-warmed oocytes to reach the blastocyst stage.